ESC Study Group of Sports Cardiology Position Paper on adverse cardiovascular effects of doping in athletes - Deligiannis, A.; Björnstad, A.; Carre, F.; Heidbüchel, H.; Kouidi, E.; Panhuyzen-Goedkoop, N. M.; Pigozzi, F.; Schänzer, W.; Vanhees, L. (European Journal of Preventive Cardiology, 2006)
The use of doping substances and methods is extensive not only among elite athletes, but also among amateur and recreational athletes. Many types of drugs are used by athletes to enhance performance, to reduce anxiety, to increase muscle mass, to reduce weight or to mask the use of other drugs during testing. However, the abuse of doping substances and methods has been associated with the occurrence of numerous health side-effects. The adverse effects depend on the type of the consumed drug, as well as the amount and duration of intake and the sensitivity of the body, since there is a large inter-individual variability in responses to a drug. Usually the doses used in sports are much higher than those used for therapeutic purposes and the use of several drugs in combination is frequent, leading to higher risk of side-effects. Among biomedical side-effects of doping, the cardiovascular ones are the most deleterious. Myocardial infarction, hyperlipidemia, hypertension, thrombosis, arrythmogenesis, heart failure and sudden cardiac death have been noted following drug abuse. This paper reviews the literature on the adverse cardiovascular effects after abuse of prohibited substances and methods in athletes, aiming to inform physicians, trainers and athletes and to discourage individuals from using drugs during sports.